Penerapan Konsep Tri Kerangka Dasar Agama Hindu dalam Penguatan Moderasi Beragama di Dusun Dopo Desa Sidomukti Kecamatan Jenawi Kabupaten Karanganyar - Gunawan; Winarsih (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
This study aims to examine the application of the Three Basic Frameworks of Hinduism in strengthening religious moderation in Dopo Hamlet, Sidomukti Village, Jenawi District, Karanganyar Regency. This study not only discusses the application of the Three Basic Frameworks of Hinduism in strengthening religious moderation, but also discusses the inhibiting and supporting factors in implementing the Three Basic Frameworks of Hinduism in strengthening religious moderation, and the impact of implementing the Three Basic Frameworks of Hinduism in Dopo Hamlet, Sidomukti Village, Jenawi District, Karanganyar Regency. To address the research questions, the author utilizes various theories and a descriptive qualitative approach to explore and explain the application of the Three Basic Frameworks of Hinduism in strengthening religious moderation. The theories used are Behaviorism and Humanism. Furthermore, the researcher also utilizes a conceptual framework, namely the Three Basic Frameworks of Hinduism, combined with efforts to strengthen religious moderation. This framework aims to identify inhibiting and supporting factors in implementing the Three Basic Frameworks of Hinduism in strengthening religious moderation.The results of this study indicate that the Three Basic Frameworks of Hinduism can strengthen religious moderation in Dopo Hamlet, Sidomukti Village, Jenawi District, Karanganyar Regency. This is evidenced by the existence of 1) differences in beliefs, and 2) cultural practices or traditions that are still practiced today, such as Nyadran (a traditional ceremony), Kenduren (a traditional ceremony), and Slametan (a religious ceremony). These traditions or cultures should be practiced exclusively by Hindus, but other communities also practice them to strengthen religious moderation in Dopo Hamlet.